2003
DOI: 10.1128/iai.71.9.4857-4861.2003
|View full text |Cite
|
Sign up to set email alerts
|

A DNA Vaccine Encoding Cu,Zn Superoxide Dismutase ofBrucella abortusInduces Protective Immunity in BALB/c Mice

Abstract: This study was conducted to evaluate the immunogenicity and protective efficacy of a DNA vaccine encoding Brucella abortus Cu,Zn superoxide dismutase (SOD). Intramuscular injection of plasmid DNA carrying the SOD gene (pcDNA-SOD) into BALB/c mice elicited both humoral and cellular immune responses. Animals injected with pcDNA-SOD developed SOD-specific antibodies which exhibited a dominance of immunoglobulin G2a (IgG2a) over IgG1. In addition, the DNA vaccine elicited a T-cell-proliferative response and also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
71
0
7

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 31 publications
4
71
0
7
Order By: Relevance
“…In this study, we found that i.m. injection of a DNA vector containing the DNA insert of Brucella p39 and sp41 was able to generate a level of protection higher than DNA vaccine encoding the L7-L12 (Kurar and Splitter 1997), sOD (Oñate et al 2003), p39 (Al-Mariri et al 2001 b ) or BAB1_0278 (SislemaEgas et al 2012), which induced a moderate protection in BALB/c mice challenged with Brucella compared to that observed in positive control mice vaccinated with live vaccine S19. In contrast, Cassataro et al (2007) found that the vaccination of BALB/c mice with the DNA vaccine coding for the chimera BLSOmp31 (pCIBLSOmp31) provided similar protection as Rev.1 against B. melitensis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found that i.m. injection of a DNA vector containing the DNA insert of Brucella p39 and sp41 was able to generate a level of protection higher than DNA vaccine encoding the L7-L12 (Kurar and Splitter 1997), sOD (Oñate et al 2003), p39 (Al-Mariri et al 2001 b ) or BAB1_0278 (SislemaEgas et al 2012), which induced a moderate protection in BALB/c mice challenged with Brucella compared to that observed in positive control mice vaccinated with live vaccine S19. In contrast, Cassataro et al (2007) found that the vaccination of BALB/c mice with the DNA vaccine coding for the chimera BLSOmp31 (pCIBLSOmp31) provided similar protection as Rev.1 against B. melitensis.…”
Section: Discussionmentioning
confidence: 99%
“…injections in the tibialis anterior muscles with 100 mg of a mixture of plasmids containing the p39 and sp41, in 50 ml sterile saline (PBS), by using a 1-mL insulin syringe with a 28-gauge needle (Weeratna et al 2001, Oñate et al 2003. The negative control groups included one group of 20 mice immunised with 100 mg pCI vector alone and one group of 20 mice treated with 100 ml of saline.…”
Section: Mice Dna Vaccination and Challengementioning
confidence: 99%
“…However, the crude antigens extracted in our method were not specific ones and therefore not useful in a highly sensitive serodiagnosis method such as ELISA [12]. Since SOD is a known antigenic protein of B. abortus [1], its potential value as a vaccine for brucellosis prevention and as a diagnostic reagent for the disease has been investigated [8,9,11], and the results in our study showed that recombinant SOD was useful for the detection of canine brucellosis. Further, since ELISA can be used for very small serum samples and handle many samples at a time, it would be suitable for the screening of valuable samples such as those from wildlife or small animals.…”
mentioning
confidence: 98%
“…Reverse vaccinology is an emerging vaccine development approach that starts with the prediction of vaccine targets using bioinformatics screening of an entire genome of a pathogenic organism (105). Vaxign is the first web-based vaccine design program that predicts vaccine targets based on reverse vaccinology.…”
Section: Bioinformatic Application and Reverse Vaccinoloymentioning
confidence: 99%